(3GdLGeY aj GdCOhjI GdeaQOIs - (3YHO Gddg Hf CMeO GdeGdbj, VjGA GdOjf, GHf GdHjWGQ , J (B646 (3g` s ((3aVd Gddg Hf eMeO GdbRhjfi s)
(3ChdgG (B:s
(3HYO GdMeO ddg aEfg deG QSeg HChGeQ GdWGYI GdYGdjI GdehdhjI dGRGdJ fGaPI ai GdeZGQH hGdeTGQb agPG cJGH GdCOhjI GdeSJYedI Ydi GdOhGe hGdCSJeQGQ s
(3BNQgG (B:s
(3hQb CPf GdZRGd EdG Cfg CUZQ jNQL ef hQbgG ai GdhSW SGbkG WhdgG CQHY CbOGe Je GdLRA GdKGfi s
(3fSNI KGfjI JGeIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B60 s
Keywords: (3GdWHs